Analysis of the Accuracy of Unattended Automated Blood Pressure Measurements and Control of Blood Pressure Thresholds: A Multicenter Cross‐Sectional Study - Shijie Yang; Zhanyang Zhou; Huanhuan Miao; Zhen Yin; Xiaochun Duan; Yuqing Zhang (The Journal of Clinical Hypertension, 2025)
ABSTRACT Accurate blood pressure measurement is fundamental for the diagnosis and management of hypertension. The emergence of u‐AOBP has been proposed as a potential alternative or complementary approach for assessing patients’ blood pressure status within clinical settings. However, robust evidence is lacking to determine its application in diagnosing hypertension within the clinical practice in China. The study involved participants recruited from October 2023 to February 2024 at three different hospitals. Participants were provided with comprehensive study information, and informed consent was obtained. Standardized, validated upper arm blood pressure monitors were used to measure blood pressure. Baseline demographic data, anthropometric measurements, u‐AOBP, and standard office blood pressure data were collected, along with additional examination results, including echocardiograms and 24‐h ambulatory blood pressure monitoring. The optimal cutoff values for diagnosing elevated blood pressure using u—AOBP, determined by ROC curve analysis with the awake ambulatory blood pressure threshold of 135/85 mmHg as the gold standard, were 130.75/83.75 mmHg (sensitivity 89.73%, specificity 27.27%). In participants with a dipper blood pressure diurnal rhythm, there was no statistically significant difference between standard office blood pressure and u‐AOBP measurements (p > 0.05). In conclusion, unattended automated office blood pressure measurement with the optimal cut‐off values for diagnosing elevated blood pressure being 130.75/83.75 mmHg, and in the population with a normal dipper circadian rhythm, the standardized u‐AOBP values can be equivalent to standard office blood pressure, but the low specificity of u‐AOBP may affect the accuracy of identifying nonhypertensive individuals.